IFAS Community Development: Defining Local Power Structures to Facilitate Leadership and Community Development - Mark A. Brennan (EDIS)
This paper is part of a series of discussions on community development. This series includes specialized papers on leadership development, civic engagement, community action, and other topics important to the development of community. This document is FCS9240, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date: March 20, 2006.